2019
DOI: 10.1128/jb.00383-19
|View full text |Cite
|
Sign up to set email alerts
|

PQS Produced by the Pseudomonas aeruginosa Stress Response Repels Swarms Away from Bacteriophage and Antibiotics

Abstract: We investigate the effect of bacteriophage infection and antibiotic treatment on the coordination of swarming, a collective form of flagellum-and pilus-mediated motility in bacteria. We show that phage infection of the opportunistic bacterial pathogen Pseudomonas aeruginosa abolishes swarming motility in the infected subpopulation and induces the release of the Pseudomonas quinolone signaling molecule PQS, which repulses uninfected subpopulations from approaching the infected area. These mechanisms have the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
86
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 68 publications
0
86
3
Order By: Relevance
“…This phenomenon was recently discovered for P. aeruginosa, where cells that were lysed by type VI secretion caused a rapid release of antibacterial compounds from neighboring kin cells (LeRoux et al 2015). Similarly, localized phage infection of P. aeruginosa can cause the affected cells to release the Pseudomonas quinolone signaling molecule (PQS), which repels other nearby cells from the infected area, constituting a response in the population that extends beyond the spatial location where the stress occurred (Bru et al 2019). To predation stresses that are very frequent, such as phage exposure, bacterial species have also adapted by producing particular biofilm matrix components that inhibit phage entry into the biofilms.…”
Section: Responses Of Biofilms To Spatially Localized Stressmentioning
confidence: 92%
“…This phenomenon was recently discovered for P. aeruginosa, where cells that were lysed by type VI secretion caused a rapid release of antibacterial compounds from neighboring kin cells (LeRoux et al 2015). Similarly, localized phage infection of P. aeruginosa can cause the affected cells to release the Pseudomonas quinolone signaling molecule (PQS), which repels other nearby cells from the infected area, constituting a response in the population that extends beyond the spatial location where the stress occurred (Bru et al 2019). To predation stresses that are very frequent, such as phage exposure, bacterial species have also adapted by producing particular biofilm matrix components that inhibit phage entry into the biofilms.…”
Section: Responses Of Biofilms To Spatially Localized Stressmentioning
confidence: 92%
“…Bacteriophages lytic against other types of bacteria (e.g., Escherichia coli (Sadekuzzaman et al, 2017;Scanlan et al, 2017;Gilcrease and Casjens, 2018), Pseudomonas aeruginosa (Tsao et al, 2018;Bru et al, 2019) and Streptococcus (Leprohon et al, 2015;Lavelle et al, 2018;Szymczak et al, 2019) have been suggested to effectively disrupt mono-biofilms formed by their respective hosts. In this study, the morphological characterization and full genomic of a novel lytic bacteriophage, IME-JL8, were presented.…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions that promote the collective movement described as swarming, PQS has been shown to promote a protective response to some antibiotic classes (but not all) ( 23 , 24 ) and also to protect against phage infection ( 24 ). These findings are also related to earlier work reporting that PQS generally limits swarming expansion ( 18 ).…”
Section: Introductionmentioning
confidence: 99%